Nilai Budaya Dan Nilai Agama Masyarakat Suku Sasak Dalam Tata Cara Pengurusan Jenazah Di Desa Kerumut Kecamatan Pringgabaya (Sebuah Studi Komparasi) - Alpan Ahmadi (Lembaga Penelitian dan Pendidikan Mandala, 2019)
This research aim to for the descreption of cultural value and religion value procedures management of corpse, thehe are some tradition executed by society which disagree with teaching of religion Islam. According to condifidence of society, people soul die not yet gone far until day the ninth, however there is still around its house, therefore, family gambled dedupe. Pursuant to problem to above obyek becoming research target is cultural value in last offices tradition in putting dedupe for people to die which is done/ conducted by society of Kerumut. Cultural value implied procedures management of the corfse in fact do not lessen existing value in religion teaching of islam. Because at the time of managing corpse from dying buried do not go out from religion teaching. Society still hold firmly with religion teaching of islam while the executed culture only left by trust is run ancestors hitherto.